The “crazy paving pattern” lung in a pregnant woman - Mohd Firdaus, Mohd Al-Baqlish; How, Soon Hin; Kuan, Yeh Chunn; Ibrahim , Aishah; Abd Ghani, Mohd Rasydan; Chan, Chee Eng; Zakaria, Alik Riasadesa; Satwi, Sapari; Loh, Tien Chi (Wiley-Blackwell, 2015)

(untitled)
Pulmonary Alveolar Proteinosis (PAP) is a rare disorder characterized by an abnormal accumulation of a PAS positive material within the alveolar spaces and distal bronchioles. A 29 year old lady in her 29th week of pregnancy presented with prolonged dry cough for two months which was associated with reduced effort tolerance and low grade fever. At presentation she is hypoxic and required oxygen supplement. She was initially treated empirically for tuberculosis but she continued to have worsening hypoxia. A high resolution CT thorax revealed a crazy paving pattern lung which was suggestive of PAP. She delivered a healthy baby at 36 weeks via an elective Caesarean section. Post operatively she underwent diagnostic bronchoalveolar lavage which showed acellular homogenous eosinophilic material which was positive for PAS/PASD and negative for mucin. Therapeutic whole lung lavage was performed and her symptoms and lung function tests improved. In this case report, we will discuss how we made the diagnosis of PAP and share our experience in managing a pregnant woman with this condition.